PRODIGAL FREEDOM AND ASYMMETRIC VIOLENCE: A DEVELOPMENT AUDIT - Palatty, Roy Varghese (Journal of Dharma, 2009)
We live in an oddly equivocal time, alternatively blasé in its developmental activities and aggressive forms of individualism. The assault on the vulnerable and fragile sections of society is at once so complete, so cruel and so clever – all encompassing and yet specifically targeted, blatantly brutal and yet unbelievably insidious – that its sheer audacity has eroded our very definition of justice. It has forced us to lower our insights, and curtail our expectations. Development has not been doing anything with oppressive idea at the beginning; it was bound to become one after being thoughtfully adopted by a series of despotic regimes as the final justification of authoritarian politics. As a product of this political process, the culture of development kills off alternative visions of desirable societies and all ‘equivocities’ against univocal identity, and thereby what occurs is the burial of “dialectic process of development.” Consequently, the post-development era has come to represent something more than resistance to a hidden structure of dominance. It now means giving back the savage the right to envision its own future. In the same way, omnipresence of violence is once again hammering our hopes and trouncing our dreams. When we analyse the root causes of terrible violence, there are different approaches available in the contemporary global milieu. Each theory has scientifically defended and systematically explained, and even thought of self-sufficient, but nevertheless keeps large space without explaining the enigmatic representations of such a phenomenon. Can we defend the Kantian view that conflicts and revolutions or wars are inevitable in human progress as “splendid misery is bound up with development of the natural predisposition in the human race”? I do not look into the ontological stimulus of violence; however, I look for empirical reasons – economic, cultural and political, in particular – although those reasons may ontologically exist in the human beings. For example, Levinas argues that ‘temptation to murder’ – to reduce the other into my subject without recognizing the dignity of the ‘otherness’ of the other – is inherent in every human individual. No one is invulnerable; anyone can be a potential racist, where extreme form of denial of the other is seen, or at least sometimes an implicit racist. Every kind of reduction whether it be ontological or existential, epistemological or metaphysical, political or social, in one way or the other, is a form of racism, where the particularities are violently, univocally, and shrewdly demolished. Differences we perceive are not norms to judge or subjugate the other. “It is not difference which makes alterity; alterity makes difference.”